Genome-Wide Selection Signals Reveal Candidate Genes Associated with Plateau Adaptation in Tibetan Sheep - Yufang Song; Chao Yuan; Xuejiao An; Tingting Guo; Wentao Zhang; Zengkui Lu; Jianbin Liu (Animals)
Tibetan sheep have developed unique adaptations for survival in the Qinghai–Tibet Plateau environment. However, the functional genes and molecular mechanisms that regulate hypoxia adaptation have not been fully characterized. In this study, based on the whole-genome resequencing data for Tibetan sheep at different altitudes, the population differentiation index (FST) and nucleotide diversity ratio (θπ ratio) were evaluated in populations of 20 Oula sheep (3501 m altitude, OL), 20 Zashijia sheep (4369 m altitude, ZSJ), and 20 Awang sheep (4643 m altitude, AW) to reveal candidate loci related to high-altitude hypoxia. We screened 728 and 524 candidate genes in the AW vs. OL and ZSJ vs. OL groups, respectively, of which 134 genes were jointly screened. Candidate genes were mainly enriched in the Ras, melanoma, melanogenesis, VEGF, and PPAR signaling pathways. HIF1AN, PDGFA, PDGFD, ANXA2, SOCS2, NOXA1, WNT7B, MMP14, GNG2, ATF6, PGAM2, PPP3R1, GSTCD, and PPARA may play important roles in the high-altitude adaptation of Tibetan sheep. In conclusion, this study provides valuable insights into the genes and molecular mechanisms that underlie high-altitude hypoxia adaptation in Tibetan sheep.